Removal of CX3R-type disinfection by-product precursors from rainwater with conventional drinking water treatment processes. (15th October 2020) - He, Jijie; Shi, Minghao; Wang, Feifei; Duan, Youli; Zhao, Tiantao; Shu, Shihu; Chu, Wenhai
Abstract: In addition to surface water and groundwater, rainwater is used as an important drinking water source in many parts of the world, especially in areas with serious water pollution or insufficient water resources. Conventional drinking water treatment technologies can remove dissolved organic matter and therefore reduce the formation of disinfection by-products (DBPs) during subsequent disinfection using surface water or groundwater as drinking water sources. However, little information has been known about the effect of conventional water treatment processes on DBP formation when rainwater is used as drinking water source. This study evaluated CX3 R-type DBP precursors removal from rainwater by conventional drinking water treatments and the corresponding decrease of CX3 R-type DBP (trihalomethanes (THMs), haloaldehydes (HALs), haloacetonitriles (HANs) and haloacetamides (HAMs)) formation and toxicity during the subsequent chlor(am)ination. The result showed that both sand filtration (SF) and activated carbon filtration (GAC) were able to remove DBP precursors and GAC outperformed SF, but no DBP precursors removal was observed during coagulation-sedimentation treatment. Among all treatments, SF + GAC was the most effective for DBP precursors removal, with removal efficiencies of 64.2% DOC, 98% DON and 76.6% UV254 . Correspondingly, both SF and GAC decreased the formation of THMs, HALs, HANs and HAMs, and GAC performed better than SF. The combination of SF and GAC, especially SF + GAC, greatly decreased DBP formation, with average reduction of 79.2% and 85% during chlorination and chloramination respectively. After different treatments, the comprehensive toxicity risk of CX3 R-type DBPs was all reduced, among which GAC + SF exhibited superior performance. Generally, the main contribution of integrated toxicity was HANs during chlor(am)ination. The formation potential of THMs, HALs, HANs and HAMs and the corresponding integrated toxicity were greater during chlorination than that during chloramination. Therefore, the combination of GAC and chloramination was promising in mitigating the comprehensive toxicity risk of THMs, HALs, HANs and HAMs for rainwater. Graphical abstract: Image 1 Highlights: We evaluate CX3 R-type DBP precursors removal from rainwater by conventional processes. Both GAC and SF removed DBP precursors from rainwater, while coagulation did not. GAC had better performance in removing DBP precursors than SF. Treatments with GAC better controlled DBP formation than SF. Treatments with GAC and NH2 Cl better decreased the overall risk of DBPs.